POLICY OF THE HEAD OF THE REGIONAL OFFICE OF THE MINISTRY OF RELIGION IN APPOINTMENT OF THE HEAD OF MADRASAH TO IMPROVE ISLAMIC EDUCATION SERVICES IN JAMBI PROVINCE - Pauzi Pauzi; Mukhtar Mukhtar; Risnita Risnita (Yayasan Literasi Kita Indonesia, 2023)
The policy of the head of the Regional Office of the Ministry of Religion in appointing Madrasa heads has not been able to improve Islamic education services in Jambi province. The results of this study indicate that the implementation of the appointment of Head of Madrasa by the Head of the Regional Office of the Ministry of Religion to improve Islamic education services in Jambi Province is in accordance with the competencies possessed by each head of Madrasa through the circular of the Secretary General of the Ministry of Religion. implementation of appointments by preparing plans, by conducting job analysis and job analysis. Both of these analyzes were carried out to obtain data regarding the formation of vacant madrasas. Implementation of selection and for appointment by the Head of the Office of the Ministry of Religion of Jambi Province with selection divided into two stages, namely administrative selection and academic selection, after administrative and academic selection is carried out, then the implementation of determining the appointment of madrasa heads, should be carried out jointly by Kanwil and Baperjakat. However, what happened was the opposite. The role of Baperjakat sometimes gets less attention and the leaders make their own policies. then in the implementation of administrative selection there are requirements that have not been fulfilled in the Regulation of the Minister of Religion of the Republic of Indonesia in the decision of the director general of Islamic Education number 5851 of 2018 and its amendment Number 3932 of 2021 concerning technical guidelines for selection and appointment of Madrasah Heads, namely having a Certificate of Completion of Education and Training ( STTPP). The conclusion of the research is that the policy of appointing madrasah heads by the Head of the Office of the Ministry of Religion of Jambi Province has not been maximized and has not accommodated the opinions and views of Baperjakat and has not implemented the Regulation of the Minister of Religion of the Republic of Indonesia on the decision of the Director General of Islamic Education which has an impact on Islamic education services that have not been fulfilled properly